‘I don’t know what normal has been’: a grounded theory exploration of the journey to endometriosis diagnosis - Babu Karavadra; Joanna Semlyen; Edward Morris; Gabrielle Thorpe (BMC Women's Health)
Abstract Background Diagnosis of endometriosis in the United Kingdom takes on average eight years, with delay to diagnosis contributing to physical, psychological and social burden for women experiencing endometriosis. This study aimed to explore experiences of diagnosis in women with confirmed endometriosis. Methods The study was informed by Constructivist Grounded Theory. Purposeful sampling was used to recruit fifteen women with confirmed endometriosis to participate in semi-structured interviews. Delay to diagnosis was identified as a key finding after analysis of four interviews and was therefore a focus for subsequent theoretical sampling. Constant comparative analysis generated codes and categories and ultimately a draft theory. Results A novel theoretical framework was developed, illustrating how participants fluctuated through four contexts of refusal, strong disbelief, weak disbelief and belief in their diagnosis journey, underpinned by a core category of ‘making sense of a fluctuating life’. Within each context, the framework explicates how relational power and self-perception engenders a strong psychosocial influence on recognition of risk of harm from symptoms of endometriosis and consequent investigating behaviour. Conclusions The journey to diagnosis of endometriosis involves a complex interplay of psychological, social and relational factors in driving or inhibiting help-seeking behaviour, requiring sensitivity, understanding and a commitment to listen and value women’s experiences within the clinical consultation to ensure timely and appropriate investigation and management.